A new species of Vittacus Keifer (Acari: Eriophyidae: Phyllocoptinae) from Qinling Area, Shaanxi Province, China - Xue, Xiao-Feng; Song, Zi-Wei; Hong, Xiao-Yue (Zootaxa, 2005)
A new species of eriophyid mite from China, Vittacus humuli sp. nov. (Phyllocoptinae: Anthocoptini) collected from Japan Hop, Humulus scandens, is described and illustrated. This new species is vagrant on leaves. A key to world species of the genus Vittacus is provided.